Peran Si terhadap Dinamika Mikroba Tanah, Nitrogen, dan Fosfor pada Berbagai Kondisi Media Tanam - Muhammad Iwan, Wahyudi; Hudaini , Hasbi; Bagus , Tripama; Saptya , Prawitasari; Oktarina, Oktarina; Bejo, Suroso (Universitas Cokroaminoto Palopo, 2025)
Abstract This study aims to analyze the effect of silicon (Si) application on soil microbial populations, particularly bacteria, nitrogen (N) and phosphorus (P) uptake under various growing media conditions, and its implications for corn (Zea mays L.) growth. The experiment used a completely randomized factorial design with two factors: Si concentration (0, 5, 10, and 15% SiO₂) and type of soil condition (standard soil, high-N soil, P-deficient soil, and high-organic-matter soil). The results showed that Si fertilizer application increased bacterial populations by 18.87% in the control medium, 134.6% in high-N soil, 134.7% in P-deficient soil, and 20% in high-organic matter soil, while the application of 15% Si in P-deficient soil increased P uptake by 53.7% compared to without Si, and in high-N soil, the application of 15% Si reduced tissue N content but increased its utilization efficiency. The increase in P uptake occurred through ionic competition between SiO₄⁴⁻ and PO₄³⁻ at the uptake site, while the decrease in tissue N content indicated Si's role in optimizing N utilization. Leaf Si content was relatively higher in all treated media compared to the control, followed by a tendency toward increased plant dry weight and stomatal number. These results indicate that Si application under nutrient stress conditions can balance N and P availability and improve physiological parameters supporting growth.